How do employees' individual learning paths differ across occupations?: A review of 10 years of empirical research. Issue 5 (9th July 2018) - Poell, Rob F.; Lundgren, Henriette; Bang, April; Justice, Sean B.; Marsick, Victoria J.; Sung, SeoYoon; Yorks, Lyle
Abstract : Purpose: Employees are increasingly expected to organize their own human resource development activities. To what extent and how exactly employees in various organizational contexts manage to shape their individual learning paths however remains largely unclear. The purpose of this present study is to explore, leaning on the empirical Learning-Network Theory (LNT) research and its findings, how employees in different occupations create learning paths that are attuned to their specific work context. Design/methodology/approach: The paper reviews 23 MSc theses based on 14 distinct data sets collected between 2005 and 2015, containing approximately 1, 484 employees from some 45 organizations and across various professions. The teachers, nurses, postal, software, telecom, railway and logistics company employees were mostly based in the Netherlands. The analysis focuses on learning-path types and learning-path strategies found in the 23 studies. Findings: Motives, themes, activities, social contexts and facilities were found to be instrumental in explaining differences among individual learning paths. A total of 34 original learning-path types and strategies were found to cluster under 12 higher-order labels. Some of these were based on learning motive, some on learning theme, some on core learning activities, some on social learning context and a few on a combination of these elements. Overall, the socially oriented learning-path strategy was the most prevalent, as it was found among nurses, employees of software/postal/telecom, railway and logistics company employees, as well as teachers in two schools. Originality/value: The paper presents the first overview of empirical studies on employee learning path(s) (strategies). In addition, it strengthens the empirical basis of the LNT.